The impact of tightening the abortion law in 2020 on fertility in Poland - Herman, Sergiusz (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
Low fertility constitutes a major demographic and economic challenge, leading to population ageing, labour shortages, and increasing pressure on social security systems. One of the factors that may influence reproductive decisions is the restrictiveness of abortion laws. The primary aim of this study is to assess whether, and to what extent, the tightening of abortion law in Poland in 2020 affected fertility, measured by the total fertility rate as well as fertility rates by women’s age group, place of residence, and relationship status. Using the augmented synthetic control method and data from 32 European countries, the study compares Poland’s actual fertility trajectory with a counterfactual scenario assuming no legal change. The results indicate that the 2020 reform contributed to a decline in fertility, particularly among women aged 15–19, married women, and urban residents. This study contributes to the limited empirical literature on the demographic effects of abortion law restrictions in Europe and demonstrates the usefulness of advanced quasiexperimental methods in evaluating the effects of public policies.